Aspects of continuous electron beam injection into a standing wave accelerating structure - Chernov, K.N.; Korchuganov, V.N.; Kuznetsov, G.I.; Makarov, I.G.; Ostreiko, G.N.; Ruvinsky, S.I.; Serdobintsev, G.V.; Tarnetsky, V.V.; Tiunov, M.A. (Вопросы атомной науки и техники, 2006)
The paper deals with processes during injection of continuous electron beam into a standing wave accelerating structure. Not all the electrons of the beam are captured into the process of acceleration. Some of them are scattered on the accelerating structure walls or return to the cathode. At short beam current pulses, it is possible to place a cathode on the system axis. In a case of high average beam power, it is necessary to inject a beam angularly to exclude hitting the cathode by returned electrons.